White-brined cheeses - Bintsis, Thomas; Alichanidis, Efstathios S.; Uzunsoy, İrem; Özer, Barbaros; Papademas, Photis; Radulovic, Zorica; Miocinovic, Jelena (My University, 2017)
This chapter discusses various white-brined cheeses, including Batzos PDO, Turkish Beyaz Peynir, Feta, Halitzia, Halloumi, Mihalic, Sjenica, and Urfa. Turkish Beyaz Peynir is a rindless, white-coloured, close-textured variety with a salty acid taste; it may have a slight piquant flavour, especially when made from sheep's milk. A number of volatile compounds are produced by defined or wild-type lactococcal bacteria used in the manufacture of Turkish Beyaz Peynir. The geographical region of Sjenica cheese production is in the Sjenicko-Pesterska plateau, which is located in the southwestern part of Serbia and represents the biggest plateau in the Balkan, which includes the municipalities Sjenica and Tutin. Sjenica cheeses are home-made cheeses, manufactured at farms or produced in small dairy craft plants. Urfa cheese variety is mainly produced from raw sheep's milk (mainly milk of the Awassi sheep breed) or an appropriate mixture of sheep's and cow's milks.
Keywords: Batzos PDO; Feta PDO; Halitzia; Halloumi cheese; Sjenica cheese; Turkish Beyaz Peynir; Urfa cheese